Control method for communication information transmission rate in passive cluster vehicles of vehicular networking. (5th August 2019) - Zhang, Rui; Guan, Zhiwei; Liu, Xiaofeng; Gao, Tingting
Aiming at the problems of high energy consumption and packet loss rate, long delay and poor fault tolerance of existing information transmission rate control methods, a practical vehicle-based passive vehicle communication information transmission rate control method is proposed. The average relative speed of vehicles and the number of neighbour vehicle nodes are selected as input parameters. The cluster head is selected by using fuzzy logic, and the cluster stability is set to the long duration of the cluster. The effective connection time model of the cluster vehicles' communication link is constructed. Taking the effective connection time model and channel capacity as constraints, the Shannon information concept and the maximum utility function are used to obtain the optimal information transmission rate of the current node. Experimental results show that the proposed method has lower-energy consumption and delay, less packet loss, and better fault-tolerant performance than the current research results.